2017
DOI: 10.1021/acs.energyfuels.7b02311
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Reconstruction of Complex Heavy Oil Molecules Using an Artificial Neural Network

Abstract: An approach for the stochastic reconstruction of petroleum fractions based on the joint use of artificial neural networks and genetic algorithms was developed. This hybrid approach reduced the time required for optimization of the composition of the petroleum fraction without sacrificing accuracy. A reasonable initial structural parameter set in the optimization space was determined using an artificial neural network. Then, the initial parameter set was optimized using a genetic algorithm. The simulations show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…If the molecule is not found in the database, it is saved in the database and invoked from the database when it is needed again. Further details of the parameters and molecule generation algorithm are given elsewhere. ,, …”
Section: Methods and Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the molecule is not found in the database, it is saved in the database and invoked from the database when it is needed again. Further details of the parameters and molecule generation algorithm are given elsewhere. ,, …”
Section: Methods and Algorithmsmentioning
confidence: 99%
“…Further details of the parameters and molecule generation algorithm are given elsewhere. 21,30,31 3.3.1. Ring Compactness Factor.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that even for freshly prepared catalysts, the active sites are usually occupied by something, they are not completely vacant, and indeed it is commonly observed that different pretreatment or “activation” of a catalyst leads to different measured conversions.If we are performing reactions on complicated feeds such as biomass, petroleum fractions, or waste plastic, we generally do not know the molecular composition of the feed, though we usually have some partial information. However, there are well‐developed “feed reconstruction” methods 73‐76 for constructing a reasonable estimate of the feed composition. Convenient affordable methods exist to solve most simple kinetic models (e.g., <100 chemical species) in common idealized reactors, in packages such as CHEMKIN 77 and CANTERA 78 . Typically the idealized reactors are 0‐d or 1‐d, sometimes 2‐d, but not three‐dimensional (3‐d).…”
Section: Technical Issuesmentioning
confidence: 99%
“…If we are performing reactions on complicated feeds such as biomass, petroleum fractions, or waste plastic, we generally do not know the molecular composition of the feed, though we usually have some partial information. However, there are well‐developed “feed reconstruction” methods 73‐76 for constructing a reasonable estimate of the feed composition.…”
Section: Technical Issuesmentioning
confidence: 99%